MAE573 : Mathematical problem solving for school / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course is designed to introduce prospective instructors to both theory and practice related to mathematical problem solving. Students will explore pedagogical issues and participate in a variety of exercises, problems, and investigations as they explore mathematics concepts from a problem solving perspective in an interactive manner. The problems are of a variety of types and may include problems involving puzzles or patterns, word problems, algebraic problems, counting and probability problems, problems dealing with geometry, and other related problems. The emphasis is on applying critical thinking skills on the exploration of various mathematics contexts to learn and teach mathematics, to solve problems, and to communicate mathematical demonstrations.